SIMULATION OF SURFACE RUNOFF REDUCTION USING SIMPLE RAIN WATER HARVESTING SYSTEM IN URBAN BUFFER AREA - Raharjo, Akhmadi Puguh (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Floods are the most common disaster in Indonesia. Among various flood types, pluvial flood is the least studied one. Simple rain water harvesting system using cistern/barrel and water tank possess the potential to reduce runoff from roofs and help alleviate the severity of pluvial flooding. The purpose of this study was to simulate the application of simple rain water harvesting in reducing surface runoff from roof surfaces in the study area within the sub Basin of Pesanggrahan. Among all the data that need to be collected were the number of houses and area of roof cover in the study area, as well as 10 years rainfall data. Number of houses per block were collected during a field survey while the estimation of roof area was conducted using a web-based software, i-Tree Canopy. From this simulation, scenario 1 (800-liter water drums), has the potential to reduce surface runoff from the roofs within the range of 6.12 to 9.07% (January) and between 5.08 to 7.49% (February). Meanwhile scenario 2 (2000-liter water tank) has the potential for surface runoff reduction which ranges between 15.30 to 22.67% (January) and between 12.64 to 18.73% (February). On the other hand, the potential to delay the initial surface runoff time using scenario 1 ranged from 3.7 to 5.5 minutes (January) and between 3.1 to 4.5 minutes (February). Meanwhile scenario 2 has a potential to delay the initial surface runoff time from 9.3 to 13.7 minutes (January) and between 7.6 to 11.3 minutes (February).